2014
DOI: 10.1159/000357866
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban for Preventing Occlusion and Restenosis after Extracranial Artery Stenting

Abstract: Background/Aims: Restenosis following extracranial artery stenting is a limitation that affects long-term outcomes. Effective and satisfying pharmacological strategies in preventing restenosis have not been established. This study aimed to evaluate whether argatroban, a direct thrombin inhibitor, could reduce the risk of in-stent restenosis after extracranial artery stenting. Methods: One hundred and fourteen patients hospitalized between August 2010 and August 2011 were enrolled. Patients were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In a recent clinical trial, 114 patients were randomized to argatroban and placebo treatments. 93 The rate of ISR in patients with argatroban was significantly lower during the 9 months follow-up. The authors suggested that intravenous administration of argatroban may be effective and safe for preventing restenosis after CAS.…”
Section: Treatment Of Irs After Casmentioning
confidence: 84%
“…In a recent clinical trial, 114 patients were randomized to argatroban and placebo treatments. 93 The rate of ISR in patients with argatroban was significantly lower during the 9 months follow-up. The authors suggested that intravenous administration of argatroban may be effective and safe for preventing restenosis after CAS.…”
Section: Treatment Of Irs After Casmentioning
confidence: 84%